Study of B and Bs mesons with a Coulomb plus exponential type potential. (21st December 2016) - Yazarloo, B. H.; Mehraban, H.
Abstract: In this paper, we have studied the B and B s mesons spectra and their decays within the framework of nonrelativistic potential model. We have considered a new potential model for the interaction of mesonic systems, the Coulomb plus exponential type potential. We have applied the perturbation approach and reported the total wave function. We have used the Nikiforov-Uvarov (NU) technique to calculate the parent wave function and thereby obtained a series solution for the perturbative wave function. Besides the decay constant and leptonic decay width, we have considered the semileptonic decay width which is related to the Isgur-Wise function. The obtained results are compared with the available experimental and theoretical data.